Community Efforts Regarding Mediation and Conciliation in Resolving Civil Disputes - Magda, Marianne; Yulistari Sitepu, Faradila (International Journal of Social Science, Education, Communication and Economics, 2024)
Resolving civil disputes through mediation and community conciliation is an effective approach to reduce the burden on the judiciary and strengthen relationships between individuals. This article discusses strategies for education, training and access to local dispute resolution centers in strengthening the community's role in resolving civil disputes. Education and training will give communities a better understanding of the mediation and conciliation process, while easy access to local dispute resolution centers will make it easier for communities to get help and support in resolving their disputes. Thus, this article discusses the efforts that need to be made to increase the role of society in resolving civil disputes, as well as the benefits that can be obtained from this strategy in strengthening social harmony and justice.